Екологічна оцінка водозабезпечення та водовідведення Агрофірми "Лісова" - Репейник, Олег Олександрович; Repeinyk, Oleh (ЦНТУ, 2021)
В роботи розглянуто системи водопостачання та водовідведення Агрофірми «Лісова». Проведено аналіз якості підземної води для потреб промивання елеватора. Надані пропозиції по покращенню підготовки підземної води для промивання елеватора. Розглянуто поводження зі стічними водами та запропоновано розділити стічні води від промивання елеватора та від свинарника з подальшим накопиченням їх в загальну вигрібну яму. The water supply and sewerage systems of the Forest Agricultural Company are considered in the work. The analysis of groundwater quality for the needs of elevator washing is carried out. Suggestions for improving the preparation of groundwater for washing the elevator. The treatment of wastewater is considered and it is proposed to separate the wastewater from the washing of the elevator and from the pigsty with their subsequent accumulation in the common cesspool.
Ecological assessment of water supply and sewerage of the Agricultural Company "Forest"
Keywords: водопостачання та водовідведення; магнітна обробка; загальна твердість; відстійник; елеватор; свинарник; water supply and drainage; magnetic treatment; total hardness; settling tank; elevator; pigsty